2019
DOI: 10.1093/jpids/piz023
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Children’s Hospital Visitor Restrictions and Healthcare-Associated Viral Respiratory Infections: A Quasi-Experimental Study

Abstract: We investigated the effect of annual winter visitor restrictions on hospital respiratory virus transmission. The healthcareassociated (HA) viral respiratory infection (VRI) transmission index (number of HA VRIs per 100 inpatient communityassociated VRIs) was 59% lower during the months in which visitor restrictions were implemented. These data prompt consideration for instituting year-round visitor restrictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Although visitor restrictions are associated with decreased healthcare‐associated respiratory infection transmission, these restrictions are typically only implemented during winter and/or influenza season. This decreased visitor burden could be the explanation for the lack of influenza, and other winter respiratory viruses, seen during this study 25 . No patients received palivizumab to prevent RSV infection.…”
Section: Discussionmentioning
confidence: 79%
“…Although visitor restrictions are associated with decreased healthcare‐associated respiratory infection transmission, these restrictions are typically only implemented during winter and/or influenza season. This decreased visitor burden could be the explanation for the lack of influenza, and other winter respiratory viruses, seen during this study 25 . No patients received palivizumab to prevent RSV infection.…”
Section: Discussionmentioning
confidence: 79%
“…Since visiting restrictions has been one out of many precautions for infection control implemented within the healthcare services during the pandemic, no study that has distinguished the effects from such precaution measures have been found. However, visitor restrictions during the winter in a paediatric hospital were found to reduce hospital transmission of respiratory viruses (not specifically SARS COv-2) compared with when no restrictions were in place ( Forkpa et al, 2020 ). Another study reported a significant reduction in health care-acquired respiratory viral infections when implementing year around visiting restrictions ( Washam et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…While visitor regulation can have a positive effect on the prevention of viral respiratory infections [ 50 , 51 ], reviews show that they can also have negative consequences for the mental and physical health of patients, the wellbeing of family members and the workload of care providers [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%